2010
DOI: 10.4103/0971-9784.69082
|View full text |Cite
|
Sign up to set email alerts
|

Is EuroSCORE applicable to Indian patients undergoing cardiac surgery?

Abstract: Indian patients undergoing cardiac surgery have different demographics, clinical profile as well as risk profile, compared to the western population. The purpose of this study was to validate the European System for Cardiac Operative Risk Evaluation (EuroSCORE) risk stratification model in Indian patients undergoing cardiac surgery in a single cardiac center. Data from 1000 consecutive adult patients undergoing cardiac surgery (coronary artery bypass grafting or valve surgery) were prospectively collected as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
(29 reference statements)
1
10
0
1
Order By: Relevance
“…The EuroSCORE overestimated mortality in patients at very high risk and there was still a tendency to overestimate mortality in low-risk patients. These findings are consistent with the most recent case series from developed countries [ 14 ] , unlike other series [ 6 - 8 ] have shown exactly the opposite.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The EuroSCORE overestimated mortality in patients at very high risk and there was still a tendency to overestimate mortality in low-risk patients. These findings are consistent with the most recent case series from developed countries [ 14 ] , unlike other series [ 6 - 8 ] have shown exactly the opposite.…”
Section: Discussionsupporting
confidence: 93%
“…External validation of the EuroSCORE in various populations around the world occurred initially with good results [ 3 - 5 ] . However, most authors have recently demonstrated that the logistic EuroSCORE overestimates the expected mortality, although some developing countries show the opposite [ 6 - 8 ] . The reasons for this discrepancy in model validation involve multiple factors: different characteristics of the exposed population, the hospitals and their treatment protocols, training teams and socioeconomic [ 9 ] differences.…”
Section: Introductionmentioning
confidence: 99%
“…This study (n = 1000) revealed good calibration and discrimination power of the score. [11] The EuroSCORE accurately predicted mortality in low and moderate risk Indian patients but under-estimated in high-risk Indian patients. In contrast, in the present study, the risk was over estimated in high-risk patients by both the scoring systems.…”
Section: Ideally Modern Stratification System Should Use Largementioning
confidence: 95%
“…18 Previous research showed that, among patients undergoing valvular surgery, the risk of death for patients in India and China with EuroSCORE values of at least 4 was similar to that for North American patients with EuroSCORE values of at least 6. 19,20 Therefore, in the current study, eligibility was extended to patients undergoing valvular surgery in Indian and Chinese centres who had a EuroSCORE value of 4 or above. Patients were excluded if an intra-aortic balloon pump was used before surgery.…”
Section: Patientsmentioning
confidence: 99%